2017
DOI: 10.1152/ajprenal.00683.2016
|View full text |Cite
|
Sign up to set email alerts
|

MIF-2/D-DT enhances proximal tubular cell regeneration through SLPI- and ATF4-dependent mechanisms

Abstract: Macrophage migration inhibitory factor (MIF) is a cytokine with pleiotropic actions that is produced by several organs and cell types. Depending on the target cell and the inflammatory context, MIF can engage its two component receptor complex CD74 and CD44 and the chemokine receptors CXCR2/4. MIF is constitutively expressed in renal proximal tubular cells, stored in intracellular preformed pools, and released at a low rate. Recently, a second MIF-like protein (i.e., MIF-2/D-DT) has been characterized in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 77 publications
1
31
0
Order By: Relevance
“…This was consistent with the pathogenic role of MIF in renal inflammatory diseases in which inhibition of MIF suppresses progressive renal injury in various forms of kidney diseases including anti‐GBM glomerulonephritis, septic shock, UUO and diabetic nephropathy . In contrast, a recent study reported that MIF is protective in AKI as high levels of plasma MIF in patients with cardiac surgery is associated with a reduced incidence of AKI and mice lacking MIF worsen AKI by inhibiting tubular epithelial cell proliferation in unilateral IRI‐induced AKI, which is also found in other two studies in which MIF or MIF‐2 inhibits AKI‐induced chronic renal injury by enhancing cell regeneration, although serum levels of creatinine are lower in MIF KO mice at 24 hours after AKI which is consistent with our finding. The reason for this discrepancy remains largely unknown.…”
Section: Disscussionsupporting
confidence: 87%
“…This was consistent with the pathogenic role of MIF in renal inflammatory diseases in which inhibition of MIF suppresses progressive renal injury in various forms of kidney diseases including anti‐GBM glomerulonephritis, septic shock, UUO and diabetic nephropathy . In contrast, a recent study reported that MIF is protective in AKI as high levels of plasma MIF in patients with cardiac surgery is associated with a reduced incidence of AKI and mice lacking MIF worsen AKI by inhibiting tubular epithelial cell proliferation in unilateral IRI‐induced AKI, which is also found in other two studies in which MIF or MIF‐2 inhibits AKI‐induced chronic renal injury by enhancing cell regeneration, although serum levels of creatinine are lower in MIF KO mice at 24 hours after AKI which is consistent with our finding. The reason for this discrepancy remains largely unknown.…”
Section: Disscussionsupporting
confidence: 87%
“…Although, SLPI was suggested to exert kidney protection via promoting tubular cell regeneration, data on the functional role of SLPI in AKI and in critically ill patients are scarce 13 . Thus, experimental studies elucidating the pathophysiological effects of SLPI on oxidative stress and kidney injury are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of oxidative stress, SLPI seems to have antioxidant and cytoprotective properties 11,12 . In a murine model of experimental ischemic AKI, Macrophage Migration Inhibitory Factor-2 (MIF-2) was suggested to exert kidney protection by upregulation of SLPI expression 13 .…”
mentioning
confidence: 99%
“…It has also been reported that the proteome profile in IR kidneys at 48 h changed by CHBP treatment was mainly related to the oxidative stress [37]. There may be differentiations between (Table 3), was renoprotective in experimental ischemia AKI [38]. SLPI inhibits nuclear factor kappa beta (NF-κB) signaling pathway [39] and the maturation of IL-1β [40], and shown as a biomarker candidate in AKI [41,42].…”
Section: Discussionmentioning
confidence: 97%